2016
DOI: 10.3390/healthcare4040080
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use and Latina Breast Cancer Survivors’ Symptoms and Functioning

Abstract: Complementary and alternative medicine (CAM) is used widely in cancer populations, particularly among women, and has shown promise for addressing symptom and functioning outcomes. Few studies to date have evaluated CAM use and associations over time with symptoms and function among Latina breast cancer survivors. We administered a baseline (N = 136) and follow-up (n = 58) telephone survey in Spanish or English assessing Latina breast cancer survivor demographics, physical function, anxiety, depression, fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In contrast, a study examining HRQOL among survivors of childhood cancers showed no statistically significant difference in spiritual well-being among Hispanics/Latinos and non-Hispanic/Latino Whites [63]. Spirituality/religious coping was associated with other aspects of HRQOL among Hispanic/Latino cancer survivors [83,158,163], including lower anxiety, fatigue, and depression [158], better functional well-being [163], and less depression [61].…”
Section: Spiritual Well-beingmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, a study examining HRQOL among survivors of childhood cancers showed no statistically significant difference in spiritual well-being among Hispanics/Latinos and non-Hispanic/Latino Whites [63]. Spirituality/religious coping was associated with other aspects of HRQOL among Hispanic/Latino cancer survivors [83,158,163], including lower anxiety, fatigue, and depression [158], better functional well-being [163], and less depression [61].…”
Section: Spiritual Well-beingmentioning
confidence: 90%
“…Fifty-nine studies examined spiritual well-being among Hispanic/Latino cancer survivors, and documented a range of religious/spiritual practices for coping with cancer, including: prayer [92,111,123,158], faith [21,36,77,84,159,160], finding meaning and peace [61,143], religious/church attendance [158], and relationship with God [22,47,63,64,94,111,[159][160][161][162]. Hispanic/Latino survivors commonly reported spirituality as a source of strength [78,86,93,101] and comfort [47,161].…”
Section: Spiritual Well-beingmentioning
confidence: 99%
“…The use of Traditional Chinese Medicine (TCM) might be one such possible strategy, which is wildly used in CRF treatment to reduce fatigue or improve the quality of life in cancer patients [ 24 ]. Yifei Sanjie pills (YFSJ), also known as “ Yiqi Chutan Tang ,” is a TCM formula used to treat lung cancer as complementary and alternative medicine, which consists of Panax quinquefolius Radix (Xi yang shen), Ranunculi Ternati Radix (Mao zhao cao), Sarcandrae Herba (Zhong jie feng), Pinelliae Rhizoma Praeparatum (Fa ban xia), Ganoderma (Ling zhi), Bombyx batryticatus (Chao jiang can), Cremastrae Pseudobulbus Pleiones Pseudobulbus (Shan ci gu), and Fritillariae Thunbergii Bulbus (Zhe bei mu).…”
Section: Introductionmentioning
confidence: 99%
“…There were not the same as results of other studies [13,44], perhaps related to different spiritual supporting environments and experiences. Only 6.5% of family members have religious faith in our study, and this is much fewer than other populations [47]. Families' behaviours or attitudes reframing or appraising the stress/situation in our research are mainly rooted in Confucian introspection, forbearance, and perseverance, but not religion [45].…”
Section: Factor Structurementioning
confidence: 90%